Generating Organic Liquid Products from Catalytic Cracking of Used Cooking Oil over Mechanically Mixed Catalysts - Onlamnao, Khajornsak; Phromphithak, Sanphawat; Tippayawong, Nakorn (International Journal of Renewable Energy Development, 2020)
Used cooking oil is unsuitable to use again in the food process, but it may be harnessed as raw material in biofuel production. In this work, used palm oil was reactedvia cracking over mechanically mixed catalystsbetween ZSM-5 and Y-Re-16to generate organic liquid products (OLP). The catalysts used were known for highacidity and lowcost for decomposition, degradation,and deoxygenation of triglycerides. The cracking experiments were conducted in a flow reactor. The experimental variables included reaction temperature between 300-500Â°C, catalyst loading between 5-20 % w/w, and ratio of mixed catalyst between ZSM-5 and Y-Re-16 from 0-100 % w/w. They were setvia response surface methodology and central composite design of experiments. Both catalysts showed good cracking reaction. The optimum condition for generating the OLP of about 85 % w/w was found at 300Â°C, 5 % catalyst loading, 97 % ratio of mixed catalyst. The OLPs with different short-chain hydrocarbons between C7-C21 were identified. The main components were 71.43% of diesel, 12.11% of gasoline, and 8.95% of kerosene-like components.